Medellín 1991. La ladera norte del Cerro del Castillo - Martín Bravo, Ana M.; Almagro- Gorbea, Martín (Complutum, 1994)
Medellín is an important oppidum of the Orientalizing Period in Iberia; its extension and chronology are similar to other turdetanian settlements. It took part of the Tartesian Culture. The settlemet was concentrated at the Cerro del Castillo as the center of the very rich territory of Vegas del Guadiana in order to control the passage of the river to the rich northwestern areas of Iberia. After the Tartesian Culture, it evolved towards a so-called “Oppida-Culture from Extremadura“. It offers a very important sequence because it had contacts with the turdetanian area untill its romanisation, when it played a important role before the foundation of Augusta Emerita.